The Tragedy of Jihad: Islamic Students’ View in North Sumatera, Medan, Indonesia - YAMAMAH, A. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study aims to find out the students´s view of the jihad concept and to identify whether or not the students understands it. A survey that involved 1000 students in 20 different universities in Medan was made. Data of the study were collected through questionnaires and analyzed both quantitative and qualitatively. The results shows that 25-35 of the students views the concept of jihad from a radicalism point of view and special attention should be given for those students and the institutions to prevent them from doing violence in the name of jihad. RESUMEN Este estudio tiene como objetivo conocer la opinión de los estudiantes sobre el concepto de yihad para identificar si los estudiantes lo entienden o no. Se realizó una encuesta que involucró a 1000 estudiantes de 20 universidades diferentes en Medan. Los datos del estudio se recogieron mediante cuestionarios y se analizaron tanto cuantitativa como cualitativamente. El resultado muestra que 25-35 presentes de los estudiantes ven el concepto de yihad desde el punto de vista del radicalismo y se debe prestar especial atención a esos estudiantes y las instituciones para evitar que cometan violencia en nombre de yihad.